Structural And Functional Prediction Of Hypothetical Proteins From Klebsiella Pneumoniae MGH78578: Molecular Modelling Studies - Choi, Sy Bing (2011)
Twenty percent of the genes from Klebsiella pneumonaie MGH78578 coded for hypothetical protein. Two particular hypothetical proteins KPN00728 and KPN00729 were identified using bioinformatics approaches. Both open reading frames showed high sequence homology to succinate dehydrogenase Chain C (SdhC) and D (SdhD) from Escherichia coli KPN00729 was annotated as SdhD in May 2008. Thus, investigation on KPN00728 remained as no annotation for SdhC gene in the complete genome sequence of Klebsiella pneumoniae MGH78578. In this study, KPN00728 has a missing region with conserved residues which is important for ubiquinone (UQ) and heme group binding. Structure and function prediction of KPN00728 coupled with secondary structure analysis and transmembrane topology showed KPN00728 adopts SDH-(subunit C)-like structure.